Raman Spectroscopy and Electrical Transport in 30Li2O• (67−x) B2O3•(x) SiO2•3Al2O3 Glasses - Amrit P. Kafle; David McKeown; Winnie Wong-Ng; Meznh Alsubaie; Manar Alenezi; Ian L. Pegg; Biprodas Dutta (Electronic Materials, 2024)
We have investigated the influence of the relative proportions of glass formers in a series of lithium alumino-borosilicate glasses with respect to electrical conductivity (σ) and glass transition temperature (Tg) as functions of glass structure, as determined using Raman spectroscopy. The ternary lithium alumino-borate glass exhibits the highest σ and lowest Tg among all the compositions of the glass series, 30Li2O•3Al2O3• (67−x) B2O3•xSiO2. However, as B2O3 is replaced by SiO2, a shallow minimum in σ, as well as a shallow maximum in Tg, are observed near x = 27, where the Raman spectra indicate that isolated diborate/tetraborate/orthoborate groups are being progressively replaced by danburite/reedmergnerite-like borosilicate network units. Overall, as the glasses become silica-rich, σ is minimized, while Tg is maximized. In general, these findings show correlations among Tg (sensitive to network polymerization), σ (proportional to ionic mobility), and the different borate and silicate glass structural units as determined using Raman spectroscopy.